Exploring halal tourism in Muslim-minority countries: Muslim travellers’ needs and concerns - Said, Mohd Fuaad; Adham, Khairul Akmaliah; Muhamad, Nur Sa’adah; Sulaiman, Syahnaz (Emerald Group Publishing, 2021)
Purpose: This study focusses on the underlying needs of Muslims to adhere to the tenets of their religion and to guide their behaviours accordingly. These requirements, for the purpose of travelling, constitute halal tourism. As Muslim-minority nations, such as Taiwan, South Korea and Japan, began to market their own brands of halal tourism, there are concerns of whether their current practices are able to meet the requirements of Muslim travellers. Thus, this study aims to understand the main needs and concerns of Muslim travellers when they visit Muslim-minority countries. Design/methodology/approach: Interviews were conducted on selected Muslim travellers who recently visited one of the following destinations, Japan, South Korea or Taiwan. Applying the process theory of travel, service marketing perspective and Muslim religious needs, the study’s conceptual framework served as the basis for crafting interview questions, selecting the participants and explaining the findings. Findings: Muslim travellers are mostly concerned with the need to perform daily prayers and to find halal food at the point of need, and willing to conduct extensive research on the destination prior to their visit. Muslim travellers’ experiences in these Muslim-minority countries are generally met with their expectations, although further socialisation with the locals is needed to induce greater overall satisfaction with the destinations. Practical implications: Understanding the current practices of halal tourism is critical so that improvements can be implemented in the industry. Originality/value: Key preparations, expectations, actual experiences in the destinations and reflections of Muslim travellers provide in-depth insights into their needs and concerns when travelling in Muslim-minority countries. The emergent religion-based dimensions in service experience, such as availability of social agents and halal food at the point of need, extend the conceptualisation of perishability and heterogeneity in service marketing literature.